KNOWLEDGE DISCOVERY IN DATABASE UNTUK MODEL ONLINE ANALYTICAL PROCESSING (OLAP) DATA KEMISKINAN - Mirza, Ahmad Haidar (JURNAL ILMIAH MATRIK, 2015)
Poverty is the main problem in developing countries, both structurally poverty, cultural and natural. That is, poverty is no longer seen as a measure of the failure of the Government to protect and fulfill the basic rights of its citizens but the nation is a challenge to realize a fair society, prosperous and sovereign. Efforts that have been implemented by the government to determine the policy measures in the effort to reduce poverty, one of them by conducting a survey to assess the poor. The results of the survey activities of these organizations obtained for the various versions of the database poverty areas or locations. The information generated from the poverty database only includes recapitulation of the poor to the area or location. To facilitate the decision-making process will require a data warehouse model that can be used as a data warehouse to extract and identify useful information for government in development planning in poverty reduction.